A Miniaturized Frequency Selective Surface Based on Square Loop Aperture Element - Wenxing Li; Chunming Wang; Yong Zhang; Yingsong Li (International Journal of Antennas and Propagation)
We propose a miniaturized band-pass frequency selective surface (FSS) with periodic unit cell structure. The proposed FSS is realized by symmetrically bending the edges of the square loop aperture element, by which our proposed FSS increases the resonant length, and, hence, reduces its size. In this FSS, each unit cell has a dimension of 0.0538λ × 0.0538λ, where λ represents the wavelength of the corresponding resonant frequency. Both the theoretical analysis and simulation results demonstrate that our proposed FSS, having high polarization stability and angle stability, can achieve smaller size in comparison with the previously proposed structures.